A Modern Guide to Food Economics - Jutta Roosen; Jill E. Hobbs (Edward Elgar Publishing, 2022)
This Modern Guide provides detailed theoretical and empirical insights to key areas of research in food economics. It takes a forward-looking perspective on how different actors in the food system shape the sustainability of food production, distribution, and consumption, as well as on major challenges to efficient and inclusive food systems. Analysing the main characteristics of modern food markets, chapters introduce readers to the economics of food systems, product differentiation, the mediating role of food retailers, and the increasing significance and complexity of international trade in food. Encapsulating new methods in the study of food consumption and policy, this Modern Guide explores changes in food value chains and consumption. It further pushes the boundaries of food economics to include economic perspectives on the role of social media and technology such as genomics in shaping food systems. Offering key insights to the state-of-the-art debates in the field, this Modern Guide will be critical reading for graduate students and researchers of food economics. It will also be a timely book for practitioners in the field wishing to take a fresh look at issues shaping food systems.
Keywords: 330; Food economics; Food policy; Food value chains; Food consumption; Innovation; Behavioural economics; Consumer behaviour; Food retailing; Ernährungsindustrie; Lebensmittelmarkt; Ernährungssicherung; Lebensmittelkonsum; Ernährungspolitik; Welt